Family physician perceptions of working with LGBTQ patients: physician training needs - Beagan, Brenda; Fredericks, Erin; Bryson, Mary (Canadian Medical Education Journal, 2015)
Background: Medical students and physicians report feeling under-prepared for working with patients who identify as lesbian, gay, bisexual, transgender or queer (LGBTQ). Understanding physician perceptions of this area of practice may aid in developing improved education. Method: In-depth interviews with 24 general practice physicians in Halifax and Vancouver, Canada, were used to explore whether, when and how the gender identity and sexual orientation of LGBTQ women were relevant to good care. Inductive thematic analysis was conducted using ATLAS.ti data analysis software. Results: Three major themes emerged: 1) Some physicians perceived that sexual/gender identity makes little or no difference; treating every patient as an individual while avoiding labels optimises care for everyone. 2) Some physicians perceived sexual/gender identity matters primarily for the provision of holistic care, and in order to address the effects of discrimination. 3) Some physicians perceived that sexual/gender identity both matters and does not matter, as they strove to balance the implications of social group membership with recognition of individual differences. Conclusions: Physicians may be ignoring important aspects of social group memberships that affect health and health care. The authors hold that individual and socio-cultural differences are both important to the provision of quality health care. Distinct from stereotypes, generalisations about social group differences can provide valuable starting points, raising useful lines of inquiry. Emphasizing this distinction in medical education may help change physician approaches to the care of LGBTQ women.